Antimetastatic Drug, Pharmacologic Challenge and Opportunity - Lu, Da-Yong; Lu, Ting-Ren (Current Drug Therapy, 2025)
Cancer is a complex and high-mortality disease in the clinic. Cancer metastasis leads to most cancer deaths. The therapeutics for cancer metastasis are greatly unsatisfactory now. Despite different types of antimetastatic agents and drugs have been reported, 90% of patients die in 5 years after metastatic nodules at secondary sites have been found.Many pharmacologic challenges and opportunities for current metastasis therapies are presented. To overcome the dilemma and shortcomings of antimetastatic treatment, medical, chemical, pharmaceutical, methodological and technical issues are integrated and highlighted. To introduce up-to-date knowledge and insights into drug targeting and pharmaceutical features and clinical paradigms, relevant drug design insights are discussed—including different pathological modes, diagnosis advances, metastatic cascade, tumor plasticity, variety of animal models, therapeutic biomarkers, computational tools and cancer genomics. Integrated knowledge, systems and therapeutics are focused.In summary, medicinal comparison, pharmaceutical innovation and clinical strategies should be increasingly investigated.
Keywords: pharmacotherapy